Analyzing And Measuring The Impact Of The Public Budget Deficit On The Trade Balance Deficit In Algeria An econometric study for the period (1998-2021) using the ARDL model - rahali, Belkacem; boultif, bilal (Journal of Research in Finance and Accounting, 2023)
This study aims to analyze and measure the impact of the public budget deficit on the trade balance deficit in Algeria during the period 1998-2021, based on the Keynesian approach in explaining the phenomenon of the twin deficits. This is achieved by examining the evolution of variables in light of the global petroleum prices and using the ARDL model and bounds testing approach to cointegration and error correction model to assess the relationship between the trade balance deficit and the public budget deficit in both the short and long terms. The study concludes several important findings, among which are: the existence of a long-term equilibrium relationship between the trade balance deficit and the public budget deficit in Algeria, the presence of a positive and significant effect of the budget deficit on the trade balance deficit in both the long and short terms. Specifically, a 1% increase in the general budget deficit as a percentage of the gross domestic product leads to a trade balance deficit increase of 0.83% and 0.23% of the output in the long and short terms respectively.